Development and Application of DNA-Based Tools to Authenticate Marketed Salvia officinalis Products - Teresa Maria Rosaria Regina; Elisa Calabrese (Sci, 2025)
Salvia officinalis (common or medicinal sage) is a highly valued member of the genus Salvia. Due to its wide range of applications in various fields, including medicine, pharmacy, cosmetics, and food, S. officinalis is a common target for economic fraud. It is imperative to implement rigorous quality control measures to ensure that fraudulent practices are prevented. Such measures should include fast and simple diagnostic tools that can also be used in the field. The objective of the present study was to ascertain the true plant composition of several Salvia-based products. This was accomplished by using PCR-RFLP and LAMP assays. In both procedures, the chloroplast trnL (UAA)-trnF (GAA) intergenic spacer served as the target analyte. The findings demonstrated the reliability and validity of the two DNA-based methods for the unequivocal identification of S. officinalis as the principal component in various sage products, as well as for the detection of irregularities (mainly the presence of adulterating species) in the production and marketing of some of these products. Nonetheless, the LAMP assay offers a more straightforward, rapid, efficient, and cost-effective approach that facilitates the authentication process for sage. The adoption of this method by quality control laboratories could then ensure safety and protect consumers from potential health risks associated with adulterated sage products.